Contribution of collagen and elastin fibers to the mechanical behavior of an abdominal connective tissue. (August 2016) - Levillain, A.; Orhant, M.; Turquier, F.; Hoc, T.
Abstract: The linea alba is a complex structure commonly involved in hernia formation. Knowledge of its mechanical behavior is essential to design suitable meshes and reduce the risk of recurrence. The aim of this study was to investigate the relationships between the mechanical properties of the linea alba and the organization of collagen and elastin fibers. For that purpose, longitudinal and transversal samples were removed from four porcine and three human linea alba, to perform tensile tests under a biphotonic confocal microscope, in each direction. Microscopic observation revealed a tissue composed of two layers, made of transversal collagen fibers in the dorsal side and oblique collagen fibers in the ventral side. This particular architecture led to an anisotropic mechanical behavior, with higher stress in the transversal direction. During loading, oblique fibers of the ventral layer reoriented toward the tensile axis in both directions, while fibers of the dorsal layer remained in the transversal direction. This rotation of oblique fibers progressively increased the stiffness of the tissue and induced a non-linear stress–stretch relation. Elastin fibers formed a layer covering the collagen fibers and followed their movement, suggesting that they ensure their elastic recoil. All of these results demonstrated the strong relationships between the microstructure and the mechanical behavior of the linea alba. Graphical abstract: Highlights: Tensile tests combined with microstructure observation were performed on linea alba. Transversal and oblique collagen fibers of this bilayer led to anisotropic behavior. Reorientation of oblique fibers toward the tensile axis induced non-linear behavior. Elastin fibers were responsible for the elastic recoil of collagen fibers.